1998
DOI: 10.1021/ja9812002
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition Reactions of Aldehydes to Tetramesityldisilene and Tetramesitylgermasilene:  Evidence for a Biradical Intermediate

Abstract: The mechanism of the addition of aldehydes to disilenes and germasilenes was investigated by examining the reaction between trans-(2-phenylcyclopropyl)carboxaldehyde and tetramesityldisilene or tetramesitylgermasilene. [Dimesityl(2-cis-4-trans-1-oxa-5-phenylpentadienyl)silyl]dimesitylsilane (1) and 2,2,3,3-tetramesityl-4-phenyloxa-2,3-disilacyclohept-6-ene (2) were formed in the reaction between the aldehyde and the disilene, and the analogous [dimesityl(2-cis-4-trans-1-oxa-5-phenylpentadienyl)silyl]dimesitylg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
22
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…7 We have used molecular probes to investigate the mechanism of the addition of carbonyl compounds to both disilenes and germasilenes. 8,9 The probes, trans-2-phenylcyclopropane carbaldehyde (1) and trans,trans-2-methoxy-3-phenylcyclopropane carbaldehyde (2), contain the same (alkoxy)phenylcyclopropylcarbinyl framework found in the hypersensitive probes developed by Newcomb. 10,11 The cyclopropane carbaldehydes are able to discriminate between the development of a radical or a cationic center at the aldehydic carbon by following different, subsequent reaction pathways.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…7 We have used molecular probes to investigate the mechanism of the addition of carbonyl compounds to both disilenes and germasilenes. 8,9 The probes, trans-2-phenylcyclopropane carbaldehyde (1) and trans,trans-2-methoxy-3-phenylcyclopropane carbaldehyde (2), contain the same (alkoxy)phenylcyclopropylcarbinyl framework found in the hypersensitive probes developed by Newcomb. 10,11 The cyclopropane carbaldehydes are able to discriminate between the development of a radical or a cationic center at the aldehydic carbon by following different, subsequent reaction pathways.…”
mentioning
confidence: 99%
“…10,11 The cyclopropane carbaldehydes are able to discriminate between the development of a radical or a cationic center at the aldehydic carbon by following different, subsequent reaction pathways. 8,9 The oxy-substituted phenylcyclopropylcarbinyl radical has been shown to undergo rapid ring-opening toward the phenyl substituent, whereas the analogous oxonium ion does not rearrange. However, in the event that the cation does undergo ring-opening, it has been shown that cleavage toward the methoxy group in the (alkoxy)phenyl-substituted cyclopropane ring will occur.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The 05606,062 and 0 1 GeiGe 2 angles are decreased respectively to 87.66(8)° and 91.09(6)°, whereas ΟδίΟ^βΣ and C 51 C 5 6Gei angles are increased to 120.5(2) and 117.8 (2). The bond distance C51-C56 (1.381(3) A) is close to that of the normal C=C double bond 5 , and the corresponding angles C^Cs-iCse (122.8(3)°) and CsiCseGe·, (117.8(2)°) are also very near to the values expected for an sp -hybridized C atom.…”
Section: Resultsmentioning
confidence: 96%